HUBUNGAN ANTARA KEMANDIRIAN BELAJAR DENGAN STRESS AKADEMIK DI SMA NEGERI 8 SURAKARTA KELAS XI IPS 1 TAHUN PELAJARAN 2021/2022 - Dewi, Ajeng Kusuma (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2023)
Abstract: This study aims to determine whether or not there is a relationship between Independent Learning and Academic Stress for students of class XI IPS 1 SMA Negeri 8 Surakarta in the academic year 2021/2022. This research is a correlational quantitative research. The population in this study were students of class XI IPS 1 for the academic year 2021/2022, totaling 36 students. The research sample used a total sampling of 36 students. Data collection techniques using questionnaires and documentation techniques. Based on the results of data analysis on Independent Learning with Academic Stress in class XI IPS 1 SMA Negeri 8 Surakarta in the 2021/2022 academic year, the calculated r value was 0.688, then the calculated r value was consulted with the r product moment table with N = 36 and a significance level of 5% and 1%, namely 0.329 and 0.424 the results of data analysis obtained that r count is greater than t table or 0.329 <0.688> 0.424 then, the Working Hypothesis (Ha) which states that